Implementation of the Project for Strengthening Pancasila Students Profiles on the Formation of Students’ Character in Class X SMA Negeri 1 Mataram - Junaidin, Junaidin; Sugino, Sugino; Sunarti, Sunarti; Romdan, Muhammad Rizky; Diniyati, Diniyati; Herdikayanti, Yenita; Arista, Widya (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The purpose of this study was to determine the Implementation of the Pancasila Learning Profile Strengthening Project on Student Character Building Class X At SMA Negeri 1 Mataram, the research method used qualitative methods. In this method, observations are made first before conducting interviews or direct observations in the field, this method is considered suitable for knowing how progressive or stages of P5 learning for learning citizens both formally and non-formally. The subjects used in this research are students at the 10th grade level of Senior High School at SMA Negeri 1 Mataram to find out how to implement the Pancasila Learner Profile in the classroom. The Pancasila Learner Profile Strengthening Project has 6 elements that we observe then it can be seen that Beriman, Bertaqwa dan kepada Tuhan Yang Maha Esa and Berahklak Mulia, Mandiri Gotong Royong, Berkhebinekaan Global and Bernalar Kritis. After being observed qualitatively, it can be concluded that this method is indeed suitable or efficient for the character building of students in class 10. After conducting research in class X SMA Negeri 1 Mataram, information was obtained that the implementation of the Pancasila Student Profile Strengthening Project on the character building of students in class X was less than optimal because there were various obstacles that caused a lack of understanding delivered by educators, including limited time that did not allow the implementation of the Pancasila Student Profile Strengthening Project